(untitled) (Nexus International Journal of Science and Education, 2024)
This study extracted the dreams and aspirations of elementary parents in the pursuit of quality of life of the elementary pupils in Maa District, Davao City. There were eight (8) elementary school parents who participated in the study. This study made use of a phenomenological approach to extract the ideas from the participants. The participants were purposely selected as representatives from the parents in the school. The virtual in-depth-interview was employed to gather information as regards to their respective experiences. Using the thematic analysis, the following themes emerged as it relates to the dreams and aspirations of the participants: the dreams and aspiration of the parents for their children were on educating their children, being healthy and happy and develop life skills for the future. The coping mechanisms of the parents were: Keeping oneself strong, being resilient and being a practical home manager. The educational management insights of the parents were: thinking positive most of the time and looking at the brighter side family situation. The elementary teachers may give their full support to the parent’s dreams and aspirations. Many of these learners may not be able to pursue their degrees, but they are being hired to work in a company, therefore it the teacher’s role to redirect their students to a much better and fruitful way of life. The parents may be given proper information and guidelines on the new school policies. The parents play an important role in educating their children disregarding their current financial challenges.They too deserved to be resilient, happy and strong. The learners may be directed well through the constant reminders of their class advisers. Their performance at school depends on their clear understanding and application of their subject matter.